2021
DOI: 10.19173/irrodl.v22i1.5110
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on Open Educational Resources to Support Interactions of Learners with Disabilities

Abstract: This scoping review explored the trends in open educational resources (OER) that support the interactions of learners with disabilities and the challenges of supporting these interactions in such environments. Emerging OER and open educational practices allow learners to interact with digital learning resources in self-regulated learning. Since OER assume learners’ self-regulation, research has explored how to promote learner interactions to facilitate better engagement and motivation. Emerging research on OER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…The design of OER itself can also hinder students' use of the materials. In terms of accessibility for students with disabilities, two recent reviews of studies on accessibility and OER demonstrated that OER still needs improvements (Moon & Park, 2021;Zhang et al, 2020). Zhang et al (2020) noted that the highest percentage of errors in OER were due to compatibility problems with assistive devices and operating systems.…”
Section: Equity Of Use and Accessmentioning
confidence: 99%
“…The design of OER itself can also hinder students' use of the materials. In terms of accessibility for students with disabilities, two recent reviews of studies on accessibility and OER demonstrated that OER still needs improvements (Moon & Park, 2021;Zhang et al, 2020). Zhang et al (2020) noted that the highest percentage of errors in OER were due to compatibility problems with assistive devices and operating systems.…”
Section: Equity Of Use and Accessmentioning
confidence: 99%
“…Some works [40,41] propose the application of Universal Design Learning (UDL). Several existing investigations on OER tend to focus on the evaluation of accessibility and usability, little attention has been paid to support the participation of students with disabilities in OER that according to the principles of UDL consider the participation of the student through of various representations [42].…”
Section: Rq1: How To Create and Manage Accessible Learning Resources?mentioning
confidence: 99%
“…The wide range of disabilities, the variability in learning, and their modes of interaction [34] suggest performing deeper analyses of the wide variety of assistive technology and their technical issues [24,48] fed back to the user experience by developing a holistic approach [51] and measuring the scope and subsequent benefits of those involved [30]. OER-based pedagogy is proposed as future research, for which, [42] points out the importance of collecting information on related instructional practices, where learning experiences are deepened.…”
Section: Rq3: What Models Have Been Used To Promote Accessibility In ...mentioning
confidence: 99%
“…There are many different OER virtual platforms and web-based OER, such as open courseware, a computing application, massive open online courses (MOOCs), social media, institutional repository, and many more ( Moon and Park, 2021 ). All these platforms promote interconnectedness globally for open access and collaboration.…”
Section: Literature Reviewmentioning
confidence: 99%